THE UTILIZATION OF WEBTOON DIGITALCOMIC IN READING COMPREHENSION: WHAT ARE THE PERCEPTIONS OF THE STUDENTS? - Savitri, Fachrina; Zaitun, Zaitun (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study aimed to analyse students' perceptions on the utilization of Webtoon digital comics media in their reading comprehension. This research used qualitative method with case study design. The data were collected by using a 5-Likert scale questionnaire and semi-structured interview asking about students"™ perception on Webtoon digital comics used as media in their reading comprehension activities. In analysing the data, each scale of the questionnaire was converted into number to measure the most preferable responses from the students, while the results of the interview was analysed in thematic analysis with coding. The finding of questionnaire analysis revealed that from the questionnaire, the students positively respond to each statement in which the highest response fell into the scale of "Agree". Meanwhile, from the interview it was found that all 4 students selected randomly from 71 also gave positive perception to Webtoon in which they said that this application helped them to comprehend the texts easier since it provided pictures and dialogue. Besides, the students also said that reading activity through Webtoon was fun and interesting. Thus, this research work concluded that the perceptions of the students toward Webtoon comic digital in their reading comprehension activity were positive.